Microencapsulation and Spray Drying of Orthosiphon Staminues - Lee Siew, Ling (2013)
The leaves of Orthosiphon Stamineus contained many useful bioactive compounds (flavonoid) that exhibit excellent therapeutic properties. However, the flavonoid contain is prone to degradation when expose to high temperature during spray drying to produce Orthosiphon Stamineus in powder form. Microencapsulation is one of the methods to preserve the flavonoids from degrading. This research is undertaken to achieve the objectives to minimize the thermal degradation of Orthosiphon Stamineus compound using spray drying method and microencapsulation method besides formulating a stable organically derived micorencapsulat to preserve the bioactive compounds from degrading. This research was conducted by extracting the bioactive compound from Orthosiphon Stamineus leaves using 70% methanol. Different concentration of the encapsulating agent, maltodextrin (MD) and whey protein isolate (WPI) were studied. The moisture, total solid and total flavonoid content test besides UPLC were analyzed. From the result obtained, 5% WPI added to the extract solution recorded the highest concentration of rosmarinic acid with amount 2.48 mg/ml and 0.00714 mg/ml. of sinensetin whereas 5% MD recorded high concentration of rosmarinic acid with amount 2.38 mg/ml and 0.00719 mg/ml sinensetin. However, 5% of WPI was a better encapsulating agent when compare to maltodextrin with its capability to achieve highest rosmarinic acid and sinensetin retention at 98.7% and 92.5% respectively. On the other hand, usage of 5% maltodextrin recorded lower rosmarinic retention (94.8%) and sinensetin (93.1%). Thus, minimize degradation of the useful bioactive components in Orthosiphon Stamineus were able to be prevented by applying the spray drying method using 5% microencapsulating agent whey protein isolate.